2021
DOI: 10.3390/pathogens10060747
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of an EHV-1 Outbreak in the United States Caused by a New H752 Genotype

Abstract: Here we report on an EHV-1 outbreak investigation caused by a novel genotype H752 (histidine in amino acid position 752 of the ORF 30 gene). The outbreak involved 31 performance horses. Horses were monitored over a period of 35 days for clinical signs, therapeutic outcome and qPCR results of EHV-1 in blood and nasal secretions. The morbidity of the EHV-1 outbreak was 84% with 26 clinically infected horses displaying fever and less frequently anorexia and distal limb edema. Four horses showed mild transient neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(63 citation statements)
references
References 24 publications
0
58
0
Order By: Relevance
“…Furthermore, two recent studies in France and the United States identified a new EHV-1 DNA polymerase (ORF30) genotype. This was followed by the isolation of a C2254/H752 which was then associated with both respiratory and neurological clinical signs [ 28 , 29 ]. Further study will investigate the presence of this new EHV-1 genotype in China’s horses.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, two recent studies in France and the United States identified a new EHV-1 DNA polymerase (ORF30) genotype. This was followed by the isolation of a C2254/H752 which was then associated with both respiratory and neurological clinical signs [ 28 , 29 ]. Further study will investigate the presence of this new EHV-1 genotype in China’s horses.…”
Section: Discussionmentioning
confidence: 99%
“…tracking the infection source and spread) and some of them were also initially thought to be pathological markers, such as the SNP identified at position 2,254 in the DNA polymerase gene (ORF 30) that was thought to be correlated with neurological disease; therefore, it was considered as a neuropathic marker (Nugent et al, 2006 ). On the basis of this point mutation, the majority of diagnostic laboratories in the USA rely solely on allelic discrimination qPCR assays to detect EHV‐1 (Pusterla et al, 2021 ).…”
Section: Assessmentmentioning
confidence: 99%
“…While EHV‐1 strains carrying the A2254 mutation are frequently (but not exclusively) isolated from abortion cases, EHV‐1 strains isolated from neurological disease cases are carrying mutation either. Recently, a third 2254 mutation (C2254) was isolated from a large outbreak in France (Sutton et al, 2020 ), and subsequently reported in the USA (Pusterla et al, 2021 ), which raised further questions on the prognostic importance of this marker (Sutton et al, 2020 ). Given this evidence, unfortunately, the molecular diagnostic approach based only on allelic discrimination, may lead to missed EHV‐1 cases as exemplified by the outbreak reported in USA (Pusterla et al, 2021 ) and by the recently reported outbreak from France (Sutton et al, 2020 ).…”
Section: Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the link between this mutation and the different forms of disease is still debated [ 9 , 10 , 11 , 12 , 13 ]. Recently, a new ORF30 variant of EHV-1 (C 2254 , coding for a histidine H 752 ), was isolated in France and the USA and associated with respiratory and neurological diseases [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%